Diverse Roles of JNK and MKK Pathways in the Brain. (8th February 2012) - Yamasaki, Tokiwa; Kawasaki, Hiroshi; Nishina, Hiroshi
Abstract : The c-Jun NH2 -terminal protein kinase (JNK) plays important roles in a broad range of physiological processes. JNK is controlled by two upstream regulators, mitogen-activated protein kinase kinase (MKK) 4 and MKK7, which are activated by various MAPKKKs. Studies employing knockout mice have demonstrated that the JNK signaling pathway is involved in diverse phenomena in the brain, regulating brain development and maintenance as well as animal metabolism and behavior. Furthermore, examination of single or combined knockout mice of Jnk1, Jnk2, and Jnk3 has revealed both functional differences and redundancy among JNK1, JNK2, and JNK3. Phenotypic differences between knockouts of MKK4 and MKK7 have also been observed, suggesting that the JNK signaling pathway in the brain has a complex nature and is intricately regulated. This paper summarizes the functional properties of the major JNK signaling components in the developing and adult brain.